2016
DOI: 10.1186/s40064-016-2016-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of salinity and temperature on uptake of perfluorinated carboxylic acids (PFCAs) by hydroponically grown wheat (Triticum aestivum L.)

Abstract: Perfluoroalkyl substances (PFASs) have recently attracted increasing concerns due to their ubiquitous existence, adverse effects and persistence in environment. This study employed four perfluorinated carboxylic acids (PFCAs) to examine effects of salinity and temperature on the PFAS uptake in wheat, one of the major crops in the North China Plain. Wheat plants were grown in the spiked-PFCA hydroponic culture system at different salinities and temperatures. As expected, salinity and temperature significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 35 publications
0
16
1
Order By: Relevance
“…Laboratory studies have suggested that short-chain perfluoroalkyls such as PFBA are more concentrated in edible portions of plants when compared to longer carbon chain substances such as PFOA or PFOS (Blaine et al 2013;2014a, 2014b. Yoo et al (2011) from the roots into the shoots by the wheat plants grown in hydroponic systems spiked with perfluorocarboxylic acids (Zhao et al 2016). Transport into the shoots also increased with decreasing carbon chain length.…”
Section: Transport and Partitioningmentioning
confidence: 93%
“…Laboratory studies have suggested that short-chain perfluoroalkyls such as PFBA are more concentrated in edible portions of plants when compared to longer carbon chain substances such as PFOA or PFOS (Blaine et al 2013;2014a, 2014b. Yoo et al (2011) from the roots into the shoots by the wheat plants grown in hydroponic systems spiked with perfluorocarboxylic acids (Zhao et al 2016). Transport into the shoots also increased with decreasing carbon chain length.…”
Section: Transport and Partitioningmentioning
confidence: 93%
“…37 Salinity and temperature were shown to be positively correlated with PFAA uptake rate, whereby this was attributed to the inuence of these variables on transpiration rate. 38 Concerning accumulation in roots, root uptake factors from soil calculated on the basis of concentrations in pore water were up to two orders of magnitude lower than root uptake factors for the same crop (lettuce) in a hydroponic exposure. This was attributed to lower sorption to the roots surface as a result of competition from other molecules in the pore water and indicates that hydroponic experiments are of limited value for studying accumulation in roots.…”
Section: Introductionmentioning
confidence: 91%
“…(2014) did not observe a pH-dependent absorption of PFOS in maize plants growing in nutrient solution, but found that PFDA had a higher accumulation at a pH 5 than at pH 7. Zhao et al. (2016) showed that the root concentration of each PFCA increased with increase in temperature, and that with a temperature increase from 20°C to 30°C, the root absorption of long-chain PFCA was faster than that of short-chain PFCA in wheat.…”
Section: Translocation Of Pfass In Soil-plant Systemmentioning
confidence: 99%